A physiologically based pharmacokinetic model of ketoconazole and its metabolites as drug-drug interaction perpetrators - Marok, Fatima; Wojtyniak, Jan-Georg; Fuhr, Laura Maria; Selzer, Dominik; Schwab, Matthias; Weiß, Johanna; Haefeli, Walter E.; Lehr, Thorsten (Pharmaceutics, 2023)
The antifungal ketoconazole, which is mainly used for dermal infections and treatment of Cushing’s syndrome, is prone to drug-food interactions (DFIs) and is well known for its strong drug-drug interaction (DDI) potential. Some of ketoconazole’s potent inhibitory activity can be attributed to its metabolites that predominantly accumulate in the liver. This work aimed to develop a whole-body physiologically based pharmacokinetic (PBPK) model of ketoconazole and its metabolites for fasted and fed states and to investigate the impact of ketoconazole’s metabolites on its DDI potential. ...